PENGARUH PENGGUNAAN APLIKASI IPUSNAS PADA PENGIKUT @LITERARYBASE DI TWITTER TERHADAP MINAT MEMBACA BUKU DIGITAL - Kala, Ynez; Ulina, Ruth Mei (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2022)
Advances in technology today, change aspects of Indonesian people's lives. Including digitization of literacy. Nowadays, many readers choose to read books digitally. There are various choices of digital reading applications. One of them is iPusnas, a free reading application managed by the Indonesian National Library. This study aims to determine the effect of using the iPusnas application on @Literarybase followers on Twitter on their interest in reading digital books. The @Literarybase account is a reading community account in Indonesia, which has hundreds of thousands of followers. The research method used is a quantitative descriptive approach. Sampling in this study used a non-probability technique involving 405 respondents. The variables of this research are